There Will Be Cooking on Mars. - Digregorio, B.E (IEEE spectrum)
This paper presents the NASA's upcoming Phoenix lander mission. Phoenix, scheduled to be launched this August and to touch down in May 2008, may resolve lingering questions about organic molecules and liquid water on Mars. It main objectives are to determine whether the Martian arctic could support life, to evaluate the history of water near the landing site, and to investigate how the planet's climate is affected by polar dynamics. Phoenix will carry TEGA (thermal and evolved gas analyzer) that could shed light on whether organics are present. Designed primarily to look at ice chemistry and carbonate minerals. TEGA can also detect organic molecules. Other instruments on Phoenix include Mars' first-ever atomic force microscope and electrochemistry instrument.